Effect of coalescence models on the prediction of the separation of dispersed oil-water pipe flows - Evripidou, Nikola; Galvanin, Federico; Angeli, Panagiota (My University, 2023)
The effect of coalescence models on the prediction of the separation of dispersed oil-water pipe flows was assessed using a one-dimensional mechanistic model. The mechanistic model predicts the formation and evolution of four characteristic layers along the pipe: a pure water layer at the bottom, a flotation/sedimentation layer, a dense-packed zone, and a pure oil layer on the top. It was shown that the film drainage coalescence model by Jeelani and Hartland (1994) that considers interfacial mobility produces good predictions at low mixture velocity, but it depends on the flowrate. The asymmetric film drainage coalescence model by Henschke et al. (2002) is independent of the mixture velocity and the dispersed-phase fraction, and produces reasonable predictions. There was small deviation between the model outputs in the presence of the four characteristic layers, but further investigation of the regions where a single dense-packed layer persists is required.
Keywords: coalescence; liquid-liquid; dispersion; separation; modelling